2008
DOI: 10.1186/1471-2490-8-19
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic relevance of interactions between venous invasion, lymph node involvement and distant metastases in renal cell carcinoma after radical nephrectomy

Abstract: BackgroundTo investigate a possible prognostic significance of interactions between lymph node invasion (LNI), synchronous distant metastases (SDM), and venous invasion (VI) adjusted for mode of detection, Eastern Cooperative Oncology Group performance status (ECOG PS), erythrocyte sedimentation rate (ESR) and tumour size (TS) in 196 patients with renal cell carcinoma treated with radical nephrectomy.MethodsMedian follow-up was 5.5 years (mean 6.9 years; range 0.01–19.4). The mode of detection, ECOG PS, ESR an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Finally, 15 studies for thrombocytosis (Bensalah et al 2006;Brookman-Amissah et al 2009;Cho et al 2008;Erdemir et al 2007;Gogus et al 2004;Ito et al 2006;Jacobsen et al 2002;Karakiewicz et al 2007;Lee et al 2006;Lehmann et al 2004;O'Keefe et al 2002;PXanz et al 2008;Ramsey et al 2008;Suppiah et al 2006;Symbas et al 2000) (Fig. 1B) and 14 studies for ESR were included (Fossa et al 1994;Kawai et al 2009;Lee et al 2006;Lehmann et al 2004;Ljungberg et al 1997;Magera et al 2008;Masuda et al 1997Masuda et al , 1998Miyata et al 2001;Roosen et al 1994;Sengupta et al 2006;Tanaka et al 2008;Tourani et al 2003;Zubac et al 2008) (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 15 studies for thrombocytosis (Bensalah et al 2006;Brookman-Amissah et al 2009;Cho et al 2008;Erdemir et al 2007;Gogus et al 2004;Ito et al 2006;Jacobsen et al 2002;Karakiewicz et al 2007;Lee et al 2006;Lehmann et al 2004;O'Keefe et al 2002;PXanz et al 2008;Ramsey et al 2008;Suppiah et al 2006;Symbas et al 2000) (Fig. 1B) and 14 studies for ESR were included (Fossa et al 1994;Kawai et al 2009;Lee et al 2006;Lehmann et al 2004;Ljungberg et al 1997;Magera et al 2008;Masuda et al 1997Masuda et al , 1998Miyata et al 2001;Roosen et al 1994;Sengupta et al 2006;Tanaka et al 2008;Tourani et al 2003;Zubac et al 2008) (Fig. 1c).…”
Section: Resultsmentioning
confidence: 99%
“…LN metastasis was an independent predictor of inferior outcome according to previous study. Zubac et al underlined that the status of the LNs was independently associated with CSS after the RN (23). Besides, Pantuck et al reported that isolated LN was associated with a poor prognosis of RN outcomes (24).…”
Section: Discussionmentioning
confidence: 99%
“…19), IL-1 (20), , and elevated erythrocyte sedimentation rate (ESR; ref. 22,23) have all been found in metastatic cancer patients and are associated with poor prognosis. Moreover, metastatic cancer patients exhibit a skewed immune polarity in that CD4 T cells are more prone to produce Th2 cytokines and less prone to produce Th1 cytokines compared with healthy age-matched volunteers (5).…”
Section: Discussionmentioning
confidence: 99%